Comparative Evaluation of Long-Term Clinical Performance and Patient Satisfaction in Zirconia Versus Lithium Disilicate Crowns: A Multi-Center Randomized Controlled Trial - Alghamdi, Mohammed Ahmed; Alanazi, Abdulmajeed Mutairan; Almujil, Abdulaziz Abdulrahman; Alanazi, Talal Ali; Alshehri, Abdullah Saleh; Altahtam, Abdulaziz Abdullah; Alrowias, Mohammad Abdullah; Alnujaidi, Suliman Abdullah; Alotaibi, Naif Mohammed; Alrashidi, Amaal Adeeb (Journal of Posthumanism, 2024)
This multi-center randomized controlled trial aimed to compare the long-term clinical performance and patient satisfaction of monolithic zirconia and lithium disilicate crowns in single-tooth restorations. A total of 240 patients requiring single full-coverage crowns were enrolled and randomly assigned to receive either a monolithic zirconia (n=120) or lithium disilicate (n=120) crown. Crowns were fabricated using standardized CAD/CAM workflows and cemented with dual-cure resin cement. Clinical evaluations were performed at baseline, 6 months, 1 year, 3 years, and 5 years using modified USPHS/FDI criteria. Patient satisfaction was assessed using a validated 7-item questionnaire. Survival analysis, chi-square tests, and repeated-measures ANOVA were used for statistical evaluation. After five years, zirconia crowns exhibited a survival rate of 89.2%, while lithium disilicate crowns showed an 84.2% survival rate (p = 0.067). Zirconia showed lower rates of fracture and chipping, particularly in posterior regions. Lithium disilicate achieved significantly higher esthetic satisfaction scores (p = 0.012) but had more mechanical complications. No significant differences were observed in comfort, function, or overall satisfaction between the two groups. Both zirconia and lithium disilicate crowns demonstrated excellent clinical outcomes and high patient satisfaction over five years. Zirconia is more suitable for high-stress posterior applications due to its superior mechanical properties, while lithium disilicate offers superior esthetics and is preferred in anterior regions. These findings support the material-specific selection of all-ceramic crowns based on clinical indication and patient expectations.